DINAMIKA POPULASI IKAN CAKALANG (KATSUWONUS PELAMIS) DI LAUT SERAM - Imanuel VT. Soukotta; Friesland Tuapetel (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2024)
This study examines the skipjack tuna fishing industry in North Seram District, Central Maluku Regency, which has been operated by local fishermen for many years. This fishery is categorized as a small-scale and concentrated effort in the Seram Sea, one of the small seas in the Indonesian archipelago, which is part of the Pacific Ocean, covering an area of approximately 12,000 square kilometers. The study employs the length-weight relationship analysis method and the von Bertalanffy growth model. The results indicate that the growth of skipjack tuna can be represented by the equation W = 0.0133L^3.0999 with a determination coefficient of 94%. The b coefficient value for the sampled skipjack tuna was 3.0999, indicating isometric growth (length and weight grow proportionally). The growth coefficient (K) of skipjack tuna was 0.17 per year, with an asymptotic length of 49.586 cm and a t0 value of -0.0748 years. The resulting von Bertalanffy equation is Lt = 49.58{1- e^-0.175(t+0.0748)}, which describes the growth pattern of skipjack tuna in the Seram Sea.